ANALISIS PROGRAM AFFILIASI SHOPEE DI MEDIA SOSIAL: literatur review - Mayla Humaira As-syiva; Natasyah; Adrian Niken Lubis; M Sahlan; Nurbaiti (CV SWA Anugerah, 2024)
This analysis will hopefully provide valuable knowledge on how to improve and optimize affiliate programs and provide recommendations for stakeholders in the e-commerce industry. Qualitative research emphasizes data quality over quantity. The data collected is considered relevant through interviews, direct observation and formal documentation and not through cues. Some solutions can be offered in overcoming the above shortcomings. First, it is imperative to improve the quality of the photos used to address the issue of product to image mismatch. In addition, to solve problems with affiliate links that don't always lead to the app, Finally, to make product reviews more completeThe conclusion from the results of the interview from the questions the researcher asked was that content creators promote products through social media Keywords: Affiliate, shopee, social media